Analysis Of The Influence Of Production, Price, Land Area And Exchange Rates On Indonesian Tobacco Exports - Lastri, Lastri; Purba, Elvis F; Sihotang, Jusmer; Laoli, Clear Rita (LPPM Universitas PGRI Sumatera Barat, 2024)
Indonesia's tobacco exports are currently experiencing a setback. For this reason, this research uses the ARDL (Autoregressive Distributed Lag) model with variables of production, land area, international prices and exchange rates which influence Indonesian Tobacco Exports both in the short and long term. For the short term, the ARDL model forecasting variables for production, land area, international prices and exchange rates have a significant effect on Indonesian tobacco exports, while for the long term the variables of international prices and exchange rates have a significant effect on Indonesian tobacco exports.